The 7 Ps of marketing and their influence in the commercial management of CITEs from Peru's agro-industrial sector - Schmidt Urdanivia, Johannes (2023)
The main objective of this research was to determine the influence of the 7 Ps of marketing in the commercial performance of public agro-industrial CITEs in Peru. However, the non-implementation of the 7 Ps of marketing by the Centers of Productive Innovation and Technology Transfer (CITE by their Spanish initials) negatively affects their commercial performance. To help improve this problem situation, an experimental study was conducted, where the 7 Ps of marketing were devised and implemented for two agro-industrial CITEs from Peru: CITE Huallaga UT Ambo and CITE Agroindustrial UT Huaura. To achieve an effective design of the 7 Ps of marketing, the results of a situational analysis of these CITEs was considered, as well as the needs and wants of their target audience. After conducting this research, it was concluded that the CITEs which implemented the 7 Ps of marketing had a better performance in the placement of technological services and an increase in the number of agro-industrial companies served, compared to previous years and to other agro-industrial CITEs which did not implement the 7 Ps of marketing.